MENEROKA PERENCANAAN BAHASA DAN LITERASI DI INDONESIA - Elis Kurniasih; Jaja Wilsa (CV. ADIBA AISHA AMIRA, 2025)
This paper aims to describe language and literacy planning in Indonesia. The language planning under study is focused on planning the Indonesian language which is positioned as the state language and national language. While literacy is focused on reading-writing literacy. Language planning is an activity carried out by the government or an agency appointed by the government to develop, foster and protect the Indonesian language. In Indonesia this body is the Language Development and Development Agency, which is then shortened to Language Agency. This agency has a vision of realizing human beings with character and becoming the nation's self through Indonesian language and literature. Many efforts have been made to pursue this vision, one of which is through the National Literacy Movement (GLN). So this paper focuses on developing, fostering, and protecting the Indonesian language and its relation to literacy conditions in Indonesia